2016
DOI: 10.1002/cctc.201600312
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selective Aliphatic C−H Silylation of 2‐Alkyloxazolines Catalyzed by Ruthenium Complexes

Abstract: The Ru‐catalyzed dehydrogenative silylation of 2‐alkyloxazolines with 1,1,1,3,5,5,5‐heptamethyltrisiloxane took place site‐selectively at methyl C(sp3)−H bonds located γ to the nitrogen atom of the oxazolyl groups. Pyridine and pyrazole rings could also be used as a directing group. A catalytic mechanism based upon successive σ‐bond metathesis is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…Finally, a C(sp 3 )–H silylation on 2-ethyloxazoline derivatives was reported by Murata and co-workers in 2016 ( Scheme 160I ). 990 The reaction was performed at 180 °C with HSi(Me)(OSiMe 3 ) 2 . This reaction did not require the use of a hydrogen acceptor, probably due to the high temperature used.…”
Section: Heterocyclic Dgs In C–h Functionalisationmentioning
confidence: 99%
“…Finally, a C(sp 3 )–H silylation on 2-ethyloxazoline derivatives was reported by Murata and co-workers in 2016 ( Scheme 160I ). 990 The reaction was performed at 180 °C with HSi(Me)(OSiMe 3 ) 2 . This reaction did not require the use of a hydrogen acceptor, probably due to the high temperature used.…”
Section: Heterocyclic Dgs In C–h Functionalisationmentioning
confidence: 99%
“…The mechanistic knowledge of this type of reaction is mainly restricted to the experimental study by Hartwig et al 21 on the Rh( i )-catalyzed silylation of arenes, and the theoretical calculations reported by Murata and co-workers on a Ru-catalysed process. 29 A plausible mechanism for an Ir( iii )-catalysed silylation reaction was proposed by Mashima et al , 19 b however, no kinetic or theoretical support for this postulation has been presented so far.…”
Section: Resultsmentioning
confidence: 99%
“…Several other catalytic dehydrogenative silylations of sp 3 C-H bonds have been directed by the nitrogen atom of heterocycles such as oxazolines, azoles and quinolines with Ru(II), Ir(III) and Ru(III) respectively, for which the nature of key ligands on the metal catalysts play a crucial role. [47][48][49] An excellent example was described by Murata 47 in 2016 who showed that the oxazoline nitrogen atom could direct the silylation of sp 3 C-H bond of the 2-alkyl group but regioselectively at the β- .nH2O also display a rather good catalytic activity for this reaction which also allows disilylation at the alkyl β-carbon atoms. (Scheme 11) 47 However the nature of the silane is crucial as HSiEt3 and HSiMe2(OMe) are not efficient for this reaction.…”
Section: The First Steps In Non Directed Catalytic Silylations Of Sp 3 C-h Bondsmentioning
confidence: 99%
“…[47][48][49] An excellent example was described by Murata 47 in 2016 who showed that the oxazoline nitrogen atom could direct the silylation of sp 3 C-H bond of the 2-alkyl group but regioselectively at the β- .nH2O also display a rather good catalytic activity for this reaction which also allows disilylation at the alkyl β-carbon atoms. (Scheme 11) 47 However the nature of the silane is crucial as HSiEt3 and HSiMe2(OMe) are not efficient for this reaction. The silylation can be extended efficiently to 2-ethylpyridine (89%) and 1-ethylpyrazole (68%).…”
Section: The First Steps In Non Directed Catalytic Silylations Of Sp 3 C-h Bondsmentioning
confidence: 99%
See 1 more Smart Citation